Late Holocene use of Kaingo Sheep Rock Shelter in the western Waterberg, Limpopo, South Africa - Wadley, Lyn; Antonites, Annie R.; Biemond, Wim; Hodgskiss, Tammy; Jacobs, Zenobia; Laue, Ghilraen; Mauran, Guilhem; Sievers, Christine; Thorp, Carolyn; Zwane, Bongekile (Southern African Humanities, 2022)
Kaingo Sheep Rock Shelter was used by Later Stone Age (LSA) hunter-gatherers between 4370±180 and 170±30 BP. The site has rock art that includes a fine-line painting of a large, fat-tailed sheep, animal finger paintings, and geometric motifs. There are many microlithic end scrapers, a few backed tools, and more than 500 complete, incomplete and broken ostrich eggshell beads, as well as grooved stones and worked bone. By ~170 BP the density of material culture items reduced and the shelter may have been used only occasionally for ritual purposes like rain-making or initiations. Hunters, herders and farmers are represented in one way or another in the shelter, but it is unclear whether residential and non-residential ‘time-share’ is involved during the contact period. Since the shelter has contemporaneous LSA and Iron Age material culture signatures, there may have been sporadic interaction between the groups. Most ceramics belong to the Eiland facies, but a few fragments of one of the earliest ceramics found in southern Africa, the Bambata facies, were also discovered. Seed and charcoal identifications reveal bushveld vegetation similar to that of today, but possible evidence for mopane trees in the last 1900 years implies greater diversity of plant life at that time.